PENGEMBANGAN MEDIA KALENDER CERITA BERBASIS CANVA MODEL PBL UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS II SDN 1 SUROKONTO WETAN KENDAL - Isna Ariyani Yuni Vita; Kurotul Aeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low interest and learning outcomes of class II students are caused by the lack of use of interesting learning media. This research aims to develop, examine the feasibility, and examine the effectiveness of the PBL model Canva-based story calendar media in increasing interest and learning outcomes in Pancasila Education for class II students at SDN 1 Surokonto Wetan, Kendal district. The research method used is Research and Development with the Bord & Gall model modified by Sugiyono with eight stages. The results of the research show that the story calendar media based on the Canva PBL model was successfully developed in increasing interest and learning outcomes in Pancasila education, material on the meaning and significance of the Pancasila symbol for class II students at SDN 1 Surokonto Wetan. The Canva PBL model based story calendar media is very suitable to be used. Validation by media experts with a score of 91.67% and material experts with a score of 87.5%. The story calendar media based on the Canva PBL model is effective in increasing the interest and learning outcomes of class II students at SDN 1 Surokonto Wetan based on the t test with a Sig value. (2-tailed) 0.000 is less than 0.05 which means rejection of H0 and acceptance of Ha. The results of the N-Gain test prove that the average interest in learning increased by 0.853 in the high category and the average pretest and posttest scores increased by 0.604 in the medium category. Canva-based story calendar media with a PBL model is very feasible and effective to apply to Pancasila education learning.